Splicing modern ropes : a practical handbook - Polman, Jan-Willem . (London, UK : Adlard Coles Nautical/Bloomsbury, 2016)
ROPEWORK, KNOTS & MACRAME. For any seafarer, splicing rope is an essential skill. But the traditional 3-strand rope is fast disappearing. So how do you splice braided rope? This is the definitive guide to this crucial skill. Most of the techniques are quite easy to master - and also fun to do. See why splices are better - and stronger - than knots or shackles for joining or shortening rope, and follow the step-by-step photographs and clear instructions to find out how to splice efficiently. Learn how to * make strong, reliable splices in braided rope * select ropes in the materials that best suit your on-board requirements * customise your ropes to make your setup easier and safer * optimise your deck layout and save weight on board * taper your sheets for ease of handling * splice an extra cover on your ropes to give better grip in clutches, avoid chafe and make them last longer While a knot can reduce the strength of a rope by as much as 50%, a well-spliced rope loses only 5-10%. The definitive guide to making strong, reliable splices in braided rope, using step-by-step photographs and clear instructions to help readers master this important but tricky skill.
Includes bibliographical references and index.
JHS
Text in English
Keywords: Ropework; Knots and splices